Blood pressure profile of primary school children in Eastern Cape province, South Africa: prevalence and risk factors - Howard Gomwe; Eunice Seekoe; Philemon Lyoka; Chioneso Show Marange (BMC, 2022)
Abstract Background The problem of cardiovascular diseases and lack of adequate information about the blood pressure profiles among children in South Africa has enormous consequences for public health and the general well-being of communities. Aim The aim of this study is to determine the blood pressure profiles and associated risk factors of primary school children in South Africa. Methods A cross sectional study was conducted among 876 children aged 9 to 14 years from 18 randomly selected schools in the Eastern Cape province of South Africa. Standardised blood pressure measuring instruments were used and an average of three readings was considered. Blood pressure status was classified according to the percentiles of systolic blood pressure (SBP). Results The overall prevalence of hypertension was 5.2% and pre-hypertension was 18.5% while normal blood pressure was 76.3%. The multilevel binary logistic regression's crude and adjusted analysis revealed that increase in age was significantly associated with elevated BP in children ([crude OR = 1.17 [1.05 - 1.29] and [adjusted OR = 1.12 [1.01 - 1.25]). In addition, increase in BMI was significantly associated with elevated BP in children ([crude OR = 1.08 [1.04 - 1.12] and [adjusted OR = 1.06 [1.02 - 1.11]). There was no statistically significant association between elevated BP and gender for both the univariate and multivariate models. There was also no statistical significant risk for elevated BP associated with place of residence. Conclusions In this sampled population the established proportion of primary school children with elevated BP is of great concern. In addition, older children and those with high BMI (that is, overweight/obesity) were associated with elevated BP. Interventions towards promoting healthy lifestyles among school learners is a necessity if we are to prevent cardiovascular diseases.